Topology, Vegetation and Stratigraphy of Far Eastern Aapa Mires (Khabarovsk Region, Russia) - Stanislav Kutenkov; Vladimir Chakov; Viktoriya Kuptsova (Land, 2022)
Aapa mires (string-flark fens) are one of the main types of mires in northern Eurasia. It has an almost continuous distribution from Scandinavia to Kamchatka, disappearing in continental climate areas and becoming one of the dominant types in more oceanic zones. This article first presents the topological features of string-flark aapa, their vegetation and peat stratigraphy related to different elements of microrelief at the southernmost borders of boreal mires of cryolithozone (51–52 N), in the Lower Amur region (Russia). String-flark fens are very similar to the aapa mires originally reported for the European North. The waterlogged minerotrophic central fen, with a ribbed surface pattern, is surrounded by oligotrophic bogs. The mosaic structure of the vegetation cover in the fens is determined by microtopography: mesooligotrophic dwarf shrub–herb–sphagnum strings, mesoeutrophic herb–sphagnum lawns, and sparse herb cover in water flarks. The flora, for the most part, corresponds with the European aapa, and has some characteristics of eastern features. We relate the localized evolution of string-flark complexes with water basin hydrology changes. The formation of string-flark complexes in pre-existing fens was preceded by the cessation of river flood waters over the surface of the mires. The further decline of erosion has led to the development of dwarf shrub–sphagnum communities containing microrelief. The immature strings of the aapa mires attest to the ongoing active change processes of the mires.